Framework de implementação estratégica para empresas vinícolas familiares da Serra Gaúcha - Schulz, Martin Ricardo (Universidade do Vale do Rio dos Sinos, 2018)
This research finds out that more difficult than formulating strategies are put action plans into practice. This is a difficulty of many companies, but particularly for the family wineries of south of Brazil, which could adopt a theoretical model capable of guiding strategic management practices and achieving corporate purposes. The focus of the study is the strategy implementation, an integrative but still little studied process that "paves the way" for the management system, allowing answers to the proposed research question: How to make strategy implementation of family wine companies effective? Therefore, the overall objective of this research is to structure a policy framework for the strategy implementation in family wineries, with specific objectives, namely: identify relevant theoretical dimensions to the study of this subject; evaluate these practices in the family wineries of south of Brazil; and shape a model as a suggestion to make the process effective in these companies. The research strategy considers as analysis unit the process of strategic execution in three wineries of the Rio Grande do Sul state, through methodologies of qualitative interviews and participant observation, in which it compares the responses of different leadership positions within these companies, to identify relevant perspectives and dimensions in the strategy implementation process. Data collection and analysis are divided into eight phases and the results enlighten two sets of elements: (1) from the leaders viewpoint of the three companies there is a set of barriers, referred as the decision-making process, the implementation of production processes; and (2) the transformation of tacit to collective knowledge capacity and the resulting family culture of these companies, determine the quality of interpersonal relationships and cross-functional process of the strategy implementation. Considering the theoretical contributions, made up of state of the art articles about the subject of this work, it is possible to identify four perspectives of strategy implementation, composed by sixteen dimensions to consider. With these elements, the researcher arranges the cultural, structural, and adaptive sets of elements, to which adds two groups of interconnectors: strategic formalization and integration. The proposed framework identifies and reorders logically the connections between the researched constructs and the factors that determine the family business dynamics in the context of strategy implementation.
Keywords: Gestão estratégica; Implementação estratégica; Empresas familiares; Execução estratégica; Cultura familiar; Framework; Strategic management; Strategy implementation; Family business; Strategy execution; Family culture; ACCNPQ::Ciências Sociais Aplicadas::Administração